2011
DOI: 10.1038/emboj.2011.229
|View full text |Cite
|
Sign up to set email alerts
|

Sunday Driver/JIP3 binds kinesin heavy chain directly and enhances its motility

Abstract: Neuronal development, function and repair critically depend on axonal transport of vesicles and protein complexes, which is mediated in part by the molecular motor kinesin-1. Adaptor proteins recruit kinesin-1 to vesicles via direct association with kinesin heavy chain (KHC), the force-generating component, or via the accessory light chain (KLC). Binding of adaptors to the motor is believed to engage the motor for microtubule-based transport. We report that the adaptor protein Sunday Driver (syd, also known as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
150
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(167 citation statements)
references
References 80 publications
13
150
2
1
Order By: Relevance
“…1C). Previous reports have shown that JIP3 concentrates in the axon tips (6,26). Our results extend this finding by examining the stages of hippocampal process outgrowth.…”
Section: Expression Of Jip3 Increases Rapidly In Hippocampal Neuronssupporting
confidence: 78%
See 2 more Smart Citations
“…1C). Previous reports have shown that JIP3 concentrates in the axon tips (6,26). Our results extend this finding by examining the stages of hippocampal process outgrowth.…”
Section: Expression Of Jip3 Increases Rapidly In Hippocampal Neuronssupporting
confidence: 78%
“…Interestingly, JIP3 is selectively expressed in the embryonic and adult mouse brains (3,4). Furthermore, the expression of JIP3 is predominantly localized in the cell bodies and axons of developing neurons and concentrates at axon tips in cultured hippocampal neurons (5,6). Together, these studies prompt the hypothesis that JIP3 might regulate axon development.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…JSAP1 and JLP may also increase kinesin-1 motor activity by enhancing kinesin-1-MT binding. Indeed, using an in vitro motility assay, Sun et al 26 showed that JSAP1 binding to KHC enhances KHC's motility along MTs. We found that the kinesin-1-MT binding was reduced in AxCANCre-infected Jsap1:Jlp dKO neurons at 3 d.p.i.…”
Section: Discussionmentioning
confidence: 99%
“…26 We used lentiviral vectors to express these wild-type and mutant JSAP1 forms as hemagglutinin (HA)-tagged proteins (designated HA-JSAP1-WT, -LZ and -ΔKBD) in primary hippocampal neurons. Although HA-JSAP1-WT, -LZ and -ΔKBD were widely distributed along the axons, double-mutant HA-JSAP1-LZ/ΔKBD failed to exit the cell body, as reported previously 26 (Figure 5a). We next conducted a time-lapse study using Jsap1:Jlp dKO neurons infected with the various HA-JSAP1 lentiviral constructs.…”
Section: Jsap1 and Jlp Regulate Axonal Transport T Sato Et Almentioning
confidence: 99%